STRUKTUR, FUNGSI, DAN NILAI NYANYIAN RAKYAT KAILI - Gazali Gazali (LITERA, 2016)
This study aims to describe structures, functions, and values in Kaili folksongs in Central Sulawesi Province. It was conducted in four regencies/cities of Donggala,Sigi Biromaru, Parigi-Mautong, and Palu. The data were collected through recording,interviews, and document study. They were analyzed by means of Ricouere’s hermeneutictheory approach supported by cultural discourse theory, critical discourse analysis,content analysis, theory of folksong functions, and componential theory of values. Thefindings are as follows. First, the structures of Kaili folksongs comprise macrostructure,superstructure, and microstructure representing Kaili people’s cultural ideology. Second,Kaili folksongs have ritual, social, educational, communicative and informative, andentertaining functions. Third, values in Kaili folksongs are religious, philosophical, ethical,and esthetic values.